Extracellular electron uptake from a cathode by the lactic acid bacterium Lactiplantibacillus plantarum - Tejedor-Sanz, Sara; Li, Siliang; Kundu, Biki Bapi; Ajo-Franklin, Caroline M. (Frontiers in Microbiology, 2023)
A subset of microorganisms that perform respiration can endogenously utilize insoluble electron donors, such as Fe(II) or a cathode, in a process called extracellular electron transfer (EET). However, it is unknown whether similar endogenous EET can be performed by primarily fermentative species like lactic acid bacteria. We report for the first time electron uptake from a cathode by Lactiplantibacillus plantarum, a primarily fermentative bacteria found in the gut of mammals and in fermented foods. L. plantarum consumed electrons from a cathode and coupled this oxidation to the reduction of both an endogenous organic (pyruvate) and an exogenous inorganic electron acceptor (nitrate). This electron uptake from a cathode reroutes glucose fermentation toward lactate degradation and provides cells with a higher viability upon sugar exhaustion. Moreover, the associated genes and cofactors indicate that this activity is mechanistically different from that one employed by lactic acid bacteria to reduce an anode and to perform respiration. Our results expand our knowledge of the diversity of electroactive species and of the metabolic and bioenergetic strategies used by lactic acid bacteria.